Effects of 5.8 GHz microwave on hippocampal synaptic plasticity of rats. Issue 10 (3rd October 2022) - Rui, Gang; Liu, Li-Yuan; Guo, Ling; Xue, Yi-Zhe; Lai, Pan-Pan; Gao, Peng; Xing, Jun-Ling; Li, Jing; Ding, Gui-Rong
ABSTRACT: Objective: 5.8 GHz spectrum is gaining more attention in wireless technology. To explore the potential hazards, we investigated the effect of exposure to 5.8 GHz microwave on learning and memory ability of rats. Methods: Morris Water maze (MWM), Novel object recognition (NOR) and Fear conditioning test (FCT) were used to evaluate the ability of spatial and non-spatial memory of rats. The hippocampal morphology, the level of brain injury factors in serum and the mitochondrial membrane potential of hippocampal neurons was examined to evaluate the damage of hippocampal neurons. The density of dendritic spines, the ultrastructure of synapses and the level of PSD95, Synaptophysin, p-CREB and CREB were detected to evaluate the hippocampal synaptic plasticity. Results: Compared with Sham group, there was no significant difference in the performance of ethology (in MWM, NOR, FCT) in Microwave 2 h group or Microwave 4 h group. The hippocampal morphology, the serum level of brain injury factors and the content of mitochondrial JC-1 monomer in Microwave 2 h group or Microwave 4 h group did not change obviously, compared with Sham group. The density of dendritic spines, the ultrastructure of synapse and the level of PSD95, Synaptophysin, p-CREB and CREB in hippocampus in Microwave 2 h group or Microwave 4 h group did not significantly change, compared with Sham group. Conclusion: Under this experimental condition, exposure to 5.8 GHz microwave could not affect the hippocampal synaptic plasticity of rats.